Determining Reduction of Diesel Fuel Consumption When Using Emulsified Biodiesel Fuels Derived from Palm Oil - Sadhik Batcha, Mohd Ansar (IRC, 2021)
Diesel fuel has been known to produce a lot of emissions that are harmful to the environment as well as to human health.